United States Indicts Chinese Military Officers for Economic Espionage. (American Journal of International Law, 2014)
The article focuses on the indictment of five Chinese military officers by the U.S. Department of Justice on May 1, 2014 for computer hacking. Topics include the cyberattacks on private targets by the Chinese government, the prevention of economic espionage in the U.S., and the threats to national security posed by computer hackers.